2022
DOI: 10.33963/kp.a2021.0185
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of coronary computed tomography angiography in patients with a high clinical likelihood of obstructive coronary artery disease

Abstract: Background:The CAT-CAD trial showed that coronary computed tomography angiography (CTA) in patients with a high prevalence of coronary artery disease (CAD) and indications for invasive coronary angiography (ICA) reduces the number of patients undergoing ICA by two-thirds and nearly eradicates non-actionable ICAs. However, the long-term benefits of this non-invasive strategy remain unknown. Aims:To evaluate the long-term efficacy and safety of a non-invasive strategy employing coronary CTA vs. ICA as the first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Coronary computed tomography angiography (CTA) is a powerful noninvasive imaging technology with a high temporal and spatial resolution that has improved risk stratification and management in patients with low-to-moderate coronary artery disease (CAD). Notably, coronary CTA is also an effective, safe, noninvasive, outpatient alternative to invasive coronary angiography (ICA) for patients with a high probability of clinically obstructive CAD ( 4 - 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coronary computed tomography angiography (CTA) is a powerful noninvasive imaging technology with a high temporal and spatial resolution that has improved risk stratification and management in patients with low-to-moderate coronary artery disease (CAD). Notably, coronary CTA is also an effective, safe, noninvasive, outpatient alternative to invasive coronary angiography (ICA) for patients with a high probability of clinically obstructive CAD ( 4 - 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, subgroup analysis did not yield any significant differences between the RCA-aorta angles of normal cases, or those with <50% and ≥50% coronary stenosis. Degree of coronary stenosis is commonly used in the current literature to characterise CAD severity (25,26,(28)(29)(30). However, this alone is not necessarily indicative of ischemic severity, which is an inherent limitation for CCTA, as the degree of coronary stenosis does not always translate to the hemodynamic significance of coronary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…CCTA clearly provides high accuracy for detecting obstructive CAD, and the high NPV determines CCTA as an effective non-invasive imaging procedure to exclude significant CAD in all risk groups, including stable symptomatic patients and those with acute coronary syndrome (17)(18)(19)(20). A previous study showed that up to 80% of ICAs can be avoided for patients with a low prevalence of CAD, since CCTA can effectively determine the need for ICA (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%